Gendered Social Stratification and Community Well-Being in Indonesia: A Systematic Literature Review - Fadhil, Muhammad; Suleman, Muh. Asharif; Selvia, Novi; Idayanti, Zulfi; Sebastian, Sheena Jane Sta. Maria (Journal of Contemporary Gender and Child Studies, 2026)
Prior systematic reviews on community well-being have predominantly focused on single-discipline approaches without integrating gendered social stratification, social interaction, and social change as a unified analytical framework, particularly in developing-country contexts such as Indonesia. Existing literature also largely examines well-being programs at the implementation level, leaving the gendered structural underpinnings of effective policy design insufficiently theorized. This study addresses these gaps through a Systematic Literature Review (SLR) of 47 peer-reviewed articles published between 2012 and 2024, sourced from Google Scholar, Scopus, and GARUDA, of which 28 met the inclusion criteria and underwent thematic analysis. The novelty lies in positioning gendered social stratification alongside social interaction and social change as three interlocking conceptual pillars, rather than isolated variables, capable of explaining how gender-based inequality reproduces poverty and social exclusion within Indonesian communities. Findings demonstrate that integrating gender-sensitive social science concepts into policy design yields more inclusive, equitable, and sustainable well-being outcomes than single-concept or gender-blind approaches. This review concludes that embedding gendered social science frameworks into policymaking is an epistemological prerequisite for achieving comprehensive community well-being in Indonesia amid globalization and technological transformation, and calls for evidence-based, cross-disciplinary collaboration between social scientists, gender advocates, policymakers, and community stakeholders.